2018
DOI: 10.1371/journal.pone.0198486
|View full text |Cite
|
Sign up to set email alerts
|

Association of bacterial genotypes and epidemiological features with treatment failure in hemodialysis patients with methicillin-resistant Staphylococcus aureus bacteremia

Abstract: ObjectivesMethicillin-resistant Staphylococcus aureus (MRSA) infections in the hemodialysis (HD) population are epidemiologically classified as healthcare-associated infections. The data about the clinical impact and bacterial characteristics of hospital-onset (HO)- and community-onset (CO)-MRSA in HD patients are scarce. The current study analyzed the difference in the clinical and molecular characteristics of HO-MRSA and CO-MRSA.MethodsWe performed a retrospective review and molecular analysis of clinical is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The dataset includes 20 different authors from Asia (n = 13), Africa (n = 5), Europe (n = 1) and America (n = 1). A total of 20 studies were included in this synthesis: seven studies employed polymerase chain reaction (PCR) for diagnosing MRSA ( 6 , 9 , 10 , 12 , 13 , 19 , 22 ), one study employed deoxyribonucleic acid (DNA) Microarray ( 7 ), two studies used DNA sequencing ( 2 , 14 ), Xpert MRSA/SA BC assay (n = 2) ( 8 , 17 ), matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF; n = 2) ( 11 , 18 ), multilocus sequence typing (MLST; n = 4) ( 15 , 20 , 23 , 24 ), GENECUBE (n = 1) ( 21 ) and staphylococcal cassette chromosome mec (SCC mec ) typing (n = 1) ( 16 ). Figure 1 is the diagrammatic flow of the study selection and list of techniques appraised in this review.…”
Section: Resultsmentioning
confidence: 99%
“…The dataset includes 20 different authors from Asia (n = 13), Africa (n = 5), Europe (n = 1) and America (n = 1). A total of 20 studies were included in this synthesis: seven studies employed polymerase chain reaction (PCR) for diagnosing MRSA ( 6 , 9 , 10 , 12 , 13 , 19 , 22 ), one study employed deoxyribonucleic acid (DNA) Microarray ( 7 ), two studies used DNA sequencing ( 2 , 14 ), Xpert MRSA/SA BC assay (n = 2) ( 8 , 17 ), matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF; n = 2) ( 11 , 18 ), multilocus sequence typing (MLST; n = 4) ( 15 , 20 , 23 , 24 ), GENECUBE (n = 1) ( 21 ) and staphylococcal cassette chromosome mec (SCC mec ) typing (n = 1) ( 16 ). Figure 1 is the diagrammatic flow of the study selection and list of techniques appraised in this review.…”
Section: Resultsmentioning
confidence: 99%
“…A surveillance study conducted across 18 provinces of China reported the dominance of ST59 between 2014 and 2019 [26], and Zhang et al reported the dominance of ST59 in MRSA isolates in Anhui Province, China, in the 2020s [27]. Nevertheless, a study performed from 2009 to 2014 in a medical center in Southern Taiwan revealed that ST239 was the most common MLST type in hemodialysis cases (23.9%), followed by ST59 (17.7%) and ST45 (13.5%); however, infections by community-associated genotypes are increasing in the hemodialysis population [11]. In the present study, ST59 was the most predominant ST in the VAI MRSA population before and even during the pandemic and was especially prevalent in TCC-MRSA during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus carriers on hemodialysis have 1.8to 4.7-fold higher risk of vascular access infections (VAIs) and bacteremia compared with noncarriers [10]. The risk of MRSA infection in hemodialysis patients is 100 times that in the general population [11]. Patients receiving hemodialysis are highly susceptible to VAIs because of their long-term necessity for vascular access, frequent puncture of vascular access sites, repeated hospitalization, frequent and long-term use of antibiotics, and immunosuppression [12].…”
Section: Introductionmentioning
confidence: 99%
“…MRSA infections are referred to as community acquired if there are no healthcare associated risks such as a recent hospitalisation or surgery, dialysis, residence in a long-term care facility, and the presence of a permanent indwelling catheter or percutaneous medical device at the time of culture [6,7]. There are increasing concerns over CA-MRSA as they cause outbreaks and are displacing nosocomial acquired MRSA as pathogens in infections [8,9]. Individuals can be carriers with no symptoms and CA-MRSA can be contracted from members of households or associations through shared facilities such as sports environment and equipment, swimming pools, clothing, and towels.…”
Section: Introductionmentioning
confidence: 99%